Pengembangan Mesin Penetas Telur Otomatis sebagai Produk Teknologi Pembelajaran Fisika - Syamsuriana Basri; Yusri Handayani (Jurnal Ilmiah Wahana Pendidikan, 2021)
This research is a development research using themethod, ADDIEnamely Analysis, Design, Development , Implementation and Evaluations, which aims to develop an automatic egg incubator as a physics learning product by applying temperature and heat material and knowing the feasibility of an automatic egg incubator. The results achieved in this study were an automatic egg incubator product that met the valid criteria, namely 89%, while the results of individual trials conducted on students gave a positive response with a percentage of 85.33% and field trials in the community gave a positive response with a percentage. 86.67% of the two trial results met the very feasible criteria.